2022
DOI: 10.1149/1945-7111/ac71d9
|View full text |Cite
|
Sign up to set email alerts
|

Review—Recent Advancements in Electrochemical Sensors for 4-Aminoquinoline Drugs Determination in Biological and Environmental Samples

Abstract: 4-Aminoquinoline including Hydroxychloroquine (HCQ), amodiaquine (AQ), Chloroquine (CQ) are a quinoline with an amino group at the fourth position with a basic side chain. They are generally used as antimalarial medications. HCQ and CQ were recommended by the World Health Organization on March 2020 for use as a possible treatment to coronavirus. Long-term administration of 4-aminoquinoline drugs can be associated with toxic side-effects on the outer retina and the retinal pigment epithelium, making their dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…69 In the literature, studies have reported that few molecules interfere with the 4-aminoquinoline assay, specifically amodiaquine. 40 This leads to the conclusion that AC−rGO@CPE exhibits good selectivity toward HCQ determination in presence of the previously mentioned species.…”
Section: Pamentioning
confidence: 79%
See 1 more Smart Citation
“…69 In the literature, studies have reported that few molecules interfere with the 4-aminoquinoline assay, specifically amodiaquine. 40 This leads to the conclusion that AC−rGO@CPE exhibits good selectivity toward HCQ determination in presence of the previously mentioned species.…”
Section: Pamentioning
confidence: 79%
“…[26][27][28] Thanks to its speed of analysis, high sensitivity, cheap cost, and low consumption of solvent, electroanalysis is advantageous compared to other analytical techniques. [29][30][31][32][33][34][35][36][37][38][39] Numerous electrochemical studies were reported for quantification of HCQ, 40 using different types of electrodes, either bare or modified such as glassy carbon electrodes (GCE), 41,42 carbon paste electrodes (CPE), 43,44 and boron-doped diamond electrodes (BDD). 45 However, the HCQ detection at electrodes showed that the oxidation overpotentials were superior, which prevents the quantification in biological and pharmaceutical samples.…”
mentioning
confidence: 99%
“…Thereby increasing the electrocatalytic activity and the selectivity of the assynthesized nanocomposite. 41,42 It displays extraordinary sensing abilities benefitting from their basal and edge plane defects concomitant with enhanced conductivity in several electrochemical investigations. 43 In our previous work, 44 we presented perovskite-type iron manganite encompassed on the surface of the functionalized nanofibre (f-CNF), which selectively sensed nimesulide associated with upsurged sensitivity and excellent reproducibility.…”
Section: Environmental Science: Nano Papermentioning
confidence: 99%
“…[10,11] And according to reports, HCQ biomolecules have a lengthy limitation half-life between one and two months. [12,13] Which will urge to develop fast and accurate analytical methods for detection and quantification of HCQ in real samples.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pharmacokinetic investigations demonstrate that a residue of HCQ over than 6.5 mg/kg per day has possible dangers to human metabolisms, including problems with the heart, outer retina, and respiration disorders [10,11] . And according to reports, HCQ biomolecules have a lengthy limitation half‐life between one and two months [12,13] . Which will urge to develop fast and accurate analytical methods for detection and quantification of HCQ in real samples.…”
Section: Introductionmentioning
confidence: 99%